Utilization of the Physics Laboratory to Increase Student Motivation and Learning Outcomes - Ayu, Ayu; Zainudin, Zainudin; Halmuniati, Halmuniati (Universitas Islam Negeri Ar-Raniry, 2025)
The minimal use of laboratory facilities by teachers means that physics learning is only carried out in the classroom. This research aims to (1) determine the use of laboratories, motivation and learning outcomes of students at SMA Negeri 6 Wangi-Wangi, (2) determine the effect of use of laboratories on learning motivation, and (3) determine the effect of use of laboratories on learning outcomes. This research was carried out using an experimental research design. This research data was taken using multiple choice questions which were then given to class XI students. The results of the research show that (1) the use of laboratories at SMA Negeri 6 Wangi-Wangi is not optimal, students have never studied in a laboratory, so their motivation and learning outcomes in physics have not reached the KKM, (2) after learning in the laboratory, the average learning motivation increased from 68.72 to 81.3, and (3) there was no difference in learning outcomes before learning in the laboratory (tcount = 2.34 < ttable = 1.72), but learning outcomes increased significantly after treatment (tcount = -35.70 < ttable = 1.72). Based on this, it can be concluded that learning in the laboratory increases students' motivation and physics learning outcomes.